STUDI KOMPARATIF PENCATATAN AKUNTANSI SESUAI SAK ETAP DENGAN PENCATATAN UMKM DI SIDOARJO - Musyafa?ah, Musyafa?ah (Jurnal Akuntansi AKUNESA, 2014)
This reseach is aimed to : 1) explain the difference between the accounting records which is used based SAK ETAP and in SMEs ; 2) identify trends in SMEs which organized accounting records in based SAK ETAP. Types of data using primary and secondary data. Financial statement analysis unit is owned SMEs and Cooperatives. Collection methods in this research were interviews and observation. Research conducted it can be concluded that there are differences between the accounting records in based accounting records SAK ETAP with SMEs and Cooperatives. Tendency Cooperative enterprises are more obedient than applying SAK ETAP UD Establishments and CV . But the format of the financial statements of the cooperative is still lacking in accordance with SAK ETAP.Keywords : SAK ETAP, SMEs, accounting record.